Euler might have known...

Geometry Level 5

A B C \triangle ABC is a right triangle ( A = 90 ) \left( \angle A=90{}^\circ \right) of height A B = 4 AB=4 , partitioned into an infinite number of adjacent triangles T i {{T}_{i}} by cevians B D i B{{D}_{i}} , i = 1 , 2 , 3 , i=1,2,3,\ldots as seen in the figure. Inside every triangle T i {{T}_{i}} , an incircle is inscribed with radius r i {{r}_{i}} . The sequence ( r i ) i N {{\left( {{r}_{i}} \right)}_{i\in \mathbb{N}}} is a geometric progression with r 1 = 1 {{r}_{1}}=1 and r 2 = 1 2 {{r}_{2}}=\dfrac{1}{2} .

If A A is the area of A B C \triangle ABC , submit 10 6 A \left\lfloor {{10}^{6}}A \right\rfloor .

Inspirations: ( 1 ) (1) , ( 2 ) (2) , ( 3 ) (3) , ( 4 ) (4) (among others)


The answer is 12695834.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Mar 11, 2021

Consider the following diagram, where the incircle of the small triangle has inradius r r , and the bases of the two right-angled triangles are x x and y y . Then we deduce that 2 ( y x ) = 1 2 [ x 2 + 16 + y 2 + 16 + y x ] r ( 4 r ) ( y x ) = r ( x 2 + 16 + y 2 + 16 ) \begin{aligned} 2(y-x) & = \; \tfrac12\big[\sqrt{x^2 + 16} + \sqrt{y^2 + 16} + y - x\big]r \\ (4 - r)(y - x) & = \; r\left(\sqrt{x^2 + 16} + \sqrt{y^2 + 16}\right) \end{aligned} and this equation can be solved to write y = 1 4 ( 2 r ) [ ( r 2 4 r + 8 ) x + r ( 4 r ) x 2 + 16 ] y \; = \; \frac{1}{4(2-r)}\left[(r^2 - 4r + 8)x + r(4-r)\sqrt{x^2 + 16}\right] Introducing the angles α , β \alpha,\beta , as shown, we deduce that tan β = 1 4 ( 2 r ) [ ( r 2 4 r + 8 ) tan α + r ( 4 r ) sin α ] \tan\beta \; = \; \frac{1}{4(2-r)}\left[(r^2 - 4r + 8)\tan\alpha + r(4-r)\sin\alpha\right]

From this we can deduce that sec β = 1 4 ( 2 r ) [ r ( 4 r ) tan α + ( r 2 4 r + 8 ) sec α ] \sec\beta \; =\; \frac{1}{4(2-r)}\left[r(4-r)\tan\alpha + (r^2 - 4r + 8)\sec\alpha \right] and hence we have tan β + sec β = 2 2 r ( tan α + sec α ) cot ( 1 2 π β ) + csc ( 1 2 π β ) = 2 2 r [ cot ( 1 2 π α ) + csc ( 1 2 π α ) ] cot ( 1 4 π 1 2 β ) = 2 2 r cot ( 1 4 π 1 2 α ) tan ( 1 4 π 1 2 β ) = ( 1 1 2 r ) tan ( 1 4 π 1 2 α ) \begin{aligned} \tan\beta + \sec\beta & = \; \frac{2}{2-r}\left(\tan\alpha + \sec\alpha\right) \\ \cot\big(\tfrac12\pi - \beta\big) + \csc\big(\tfrac12\pi - \beta\big) & = \; \frac{2}{2-r}\left[\cot\big(\tfrac12\pi - \alpha\big) + \csc\big(\tfrac12\pi - \alpha\big)\right] \\ \cot\left(\tfrac14\pi - \tfrac12\beta\right) & = \; \frac{2}{2-r}\cot\left(\tfrac14\pi - \tfrac12\alpha\right) \\ \tan\left(\tfrac14\pi - \tfrac12\beta\right) & = \; \left(1 - \tfrac12r\right)\tan\left(\tfrac14\pi - \tfrac12\alpha\right) \end{aligned} If we define θ n = A B D n \theta_n = \angle ABD_n to be the angle at the top of the triangle A B D n ABD_n , we deduce that tan ( 1 4 π 1 2 θ n ) = ( 1 1 2 r n ) tan ( 1 4 π 1 2 θ n 1 ) \tan\left(\tfrac14\pi - \tfrac12\theta_n\right) \; = \; \left(1 - \tfrac12r_n\right)\tan\left(\tfrac14\pi - \tfrac12\theta_{n-1}\right) for any n 2 n \ge 2 . If θ = A B C \theta_\infty = \angle ABC is the angle at the top vertex of the limiting triangle A B C ABC , it follows from this that tan ( 1 4 π 1 2 θ ) = tan ( 1 4 π 1 2 θ 1 ) × n = 2 ( 1 1 2 r n ) \tan\left(\tfrac14\pi - \tfrac12\theta_\infty\right) \; = \; \tan\left(\tfrac14\pi - \tfrac12\theta_1\right) \times \prod_{n=2}^\infty \left(1 - \tfrac12r_n\right) Now tan θ 1 = 3 4 \tan\theta_1 = \tfrac34 , so that tan 1 2 θ 1 = 1 3 \tan\tfrac12\theta_1 = \tfrac13 , and hence tan ( 1 4 π 1 2 θ 1 ) = 1 2 \tan\left(\tfrac14\pi - \tfrac12\theta_1\right) = \tfrac12 . Thus we deduce that tan ( 1 4 π 1 2 θ ) = n = 1 ( 1 2 n ) = ( 1 2 ; 1 2 ) \tan\left(\tfrac14\pi - \tfrac12\theta_\infty\right) \; = \; \prod_{n=1}^\infty \left(1 - 2^{-n}\right) \; =\; \big(\tfrac12\,;\,\tfrac12\big)_\infty where ( 1 2 , 1 2 ) \big(\tfrac12,\tfrac12\big)_\infty is the q q -Pochhammer symbol. Thus we deduce that tan ( 1 2 θ ) = 1 ( 1 2 ; 1 2 ) 1 + ( 1 2 ; 1 2 ) tan θ = 1 2 ( 1 ( 1 2 ; 1 2 ) ( 1 2 ; 1 2 ) ) \begin{aligned} \tan\big(\tfrac12\theta_\infty\big) & = \; \frac{1 - \big(\tfrac12\,;\,\tfrac12\big)_\infty}{1 + \big(\tfrac12\,;\,\tfrac12\big)_\infty} \\ \tan\theta_\infty & = \; \frac12\left(\frac{1}{\big(\tfrac12\,;\,\tfrac12\big)_\infty} - \big(\tfrac12\,;\,\tfrac12\big)_\infty\right) \end{aligned} and so the area of the triangle A B C ABC is Δ = 8 tan θ = 4 ( 1 ( 1 2 ; 1 2 ) ( 1 2 ; 1 2 ) ) = 12.6958340974738... \Delta \; =\; 8\tan\theta_\infty \; = \; 4\left(\frac{1}{\big(\tfrac12\,;\,\tfrac12\big)_\infty} - \big(\tfrac12\,;\,\tfrac12\big)_\infty\right) \; = \; 12.6958340974738... and hence 1 0 6 Δ = 12695834 \lfloor 10^6 \Delta \rfloor = \boxed{12695834} .

Excellent!

Thanos Petropoulos - 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...